Twenty-Five Years of the Brazilian Cybersecurity Symposium (SBSeg): A Retrospective Review - Quincozes, Silvio E.; Quincozes, Camilla B.; Souza, Paulo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
The Brazilian Cybersecurity Symposium (SBSeg) reached its twenty-fifth edition in 2025, reflecting the evolution of cybersecurity research in Brazil. This paper presents an article-level longitudinal survey of the SBSeg main track from 2001 to 2025, covering 25 proceedings volumes and 824 papers. We analyze the corpus through three axes: community formation, research agenda, and methodological maturity. Specifically, we examine who published in the venue, which topics structured its scientific agenda, and how research practices evolved across prototypes, datasets, empirical evaluation, formal methods, machine learning, vulnerability analysis, and user-centered studies. The results show SBSeg’s transition from information and computer systems security to a broader cybersecurity forum, preserving foundational areas while incorporating new waves such as privacy, IoT, blockchain, post-quantum cryptography, adversarial machine learning, and generative AI.